Urban Planning and Its Role in Reducing Crime: A Theoretical Study in the Mosul City - Abdulaziz, Ahmad Abdulaziz; Alsabaawi, Yousif Hamid (Al-Adab Journal, 2021)
In spite of the progress achieved by the country at all levels, namely the urban planning-our research subject-the master plans, which although made urban life easier in terms of the spatial (physical) aspect have considerable deficit concerning the social (moral) aspects. Most cities have now become excellent, but with no spirit, and the people are living in social and psychological isolation maintaining trivial relations with their closest spatial neighbor. Today, the situation is almost the same in all Iraqi cities, including the city of Mosul-the study area. The planning-decision makers tried to embody the design ideas of the western city planners so that Iraqi cities could become the most beautiful Arab cities during the mid-period of the last century and the city of Mosul the most attractive city in Iraq. However, during planning, they neglected the social aspect, which is of great significance to the Iraqi - Arab individuals who want to have close social relations with their spatial and social surroundings. But today they live in social and psychological isolation that has forced them to retreat into a shell with his family. What further complicated the situation in the city of Mosul was the number of unpleasant events experienced by the city, especially after the American occupation of Iraq in 2003. During that time, there was complete security paralysis, innocent people were killed, and organized crime was rampant, leading to a drastic increase in the crime rate. Besides, the events of the ISIS invasion of Mosul in 2014 and the liberation war against ISIS in 2017 played a crucial role in the destruction of the planning and social infrastructure of the city of Mosul. This warranted that the researchers provide suitable ideas to those in charge of city planning and re-development, and offer them the best designs for the city of Mosul taking into consideration the physical and social aspects.